PROFIL KESALAHAN PEMECAHAN MASALAH KESEBANGUNAN DITINJAU DARI KEPERCAYAAN DIRI DAN KECEMASAN MATEMATIKA - Prabowo, Haniftia Haqqiendini; RIYADI, RIYADI; SUBANTI, SRI (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
The aims from this research are to describe the mistake of solving kesebangunan problems in terms of the self confidence and mathematics anxiety of junior high school students. This type of this research is qualitative descriptive. The main data of this research are test results, self-confidence questionnaires results, mathematics anxiety questionnaires results and interviews results. The subject of this research are the students who have low, medium and high self-confidence with low, medium and high mathematics anxiety. The student will be given a test to find out the mistakes. Interviews were conducted to students who made the most mistakes. The results of this research indicated that students who have low, medium or high self-confidence with low, medium or high math anxiety make a mistake of concept at the stage of formulating strategies to solve problems. The mistake of strategy that many students made were removing unit data in the arithmetic operation process at the stage of implementing the planned strategy. The other mistakes made were a mistake of strategy in the stage of carry out the planned strategy and a mistake of counting operations in the stage of re-examination occurred in each group.